Analisis Laporan Keuangan Di Era Digital: Tantangan Dan Peluang Bagi Perusahaan Modern (Studi Review Jurnal) - Cristanti Panjaitan; Salshabilla Nayma; Intan Afriliyani; Fitri Yani Panggabean (CV. ITTC INDONESIA, 2025)
Digital transformation has brought about fundamental changes in corporate financial reporting. Technologies such as cloud computing, big data, and ERP are now utilised in the process of recording and presenting financial information. This research aims to examine in depth the influence of digitalisation on modern corporate financial reporting using a literature study approach. Eight national and international journals were used as the basis of analysis, covering issues such as efficiency, transparency, data security, and human resource readiness. The study results show that digitisation has a positive impact on reporting speed, information accuracy, and investor confidence. However, the main challenges still revolve around data security and the readiness of technology and human resources, especially in MSMEs. This study provides strategic recommendations in the form of strengthening digital infrastructure, human resource training, and regulations that support digital-based financial reporting. It is hoped that the results of this study can contribute to encouraging broader and safer digital transformation in the financial sector. Similar research was also conducted by Aprilia, Damanik, and Panggabean (2024) which highlighted the importance of applying appropriate accounting standards in the preparation of MSME financial reports.